CLDN14 is epigenetically silenced by EZH2-mediated H3K27ME3 and is a novel prognostic biomarker in hepatocellular carcinoma. (31st March 2016) - Li, Chang-Peng; Cai, Mu-Yan; Jiang, Li-Juan; Mai, Shi-Juan; Chen, Jie-Wei; Wang, Feng-Wei; Liao, Yi-Ji; Chen, Wen-Hui; Jin, Xiao-Han; Pei, Xiao-Qing; Guan, Xin-Yuan; Zeng, Mu-Sheng; et al.
Summary: Our article uncovered that CLDN14 is modified by EZH2-mediated H3K27ME3, and provided an explanation for the aggressive nature of HCC with downregulation of CLDN14 and the underling mechanism that links the tumor suppressor CLDN14 to the wnt/β-catenin signaling pathway. Abstract: Trimethylation of lysine 27 on histone H3 (H3K27ME3) is a transcription-suppressive histone mark mediated by enhancer of zeste homolog 2 (EZH2). We have previously suggested that EZH2-mediated H3K27ME3 plays a critical oncogenic role in human hepatocellular carcinoma (HCC) aggressiveness. However, the direct downstream targets of EZH2-H3K27ME3 and the molecular mechanisms by which regulates HCC pathogenesis remain unclear. In this study, we used chromatin immunoprecipitation together with high-throughput sequencing (ChIP-seq) and gene expression profiling by microarray analysis to assess genome-wide chromatin occupancy of H3K27ME3 in HCC cells. We identified that claudin14 (CLDN14) is a potentially direct target for EZH2-mediated H3K27ME3 in HCC. In a large cohort of clinical HCC tissues, we found that low expression of CLDN14 was significantly associated with advanced tumor stage and determined to be an independent predictor of shortened survival of HCC patients. Next, functional experiment demonstrated that depletion of CLDN14 substantially restored EZH2-silenced HCC cells motility and invasive capacities and supported cell epithelial–mesenchymal transition (EMT). Furthermore, downregulation of CLDN14 dramatically re-enhanced the wnt/β-catenin signaling activity in EZH2-silenced HCC cells by increasing the levels of active β-catenin and promoting the nuclear localization of β-catenin. These results, collectively, uncover that CLDN14 is a novel direct target of EZH2-mediated H3K27ME3, and provide an explanation for the aggressive nature of HCC with downregulation of CLDN14 and the underling mechanism that links the tumor suppressor CLDN14 to the wnt/β-catenin signaling pathway.